Dancing the demons away dance movement therapy as a tool in counseling sexually abused children - Baraero, Dinghy Kristine M.; Ho, Leticia P.; Soria, Robinson C.; De Guzman, Ligaya S.; Fajardo, Amelia C.; Guererro, Sylvia H. (2005)
This research investigated the effects of Dance/Movement Therapy (DMT) as a therapeutic intervention among sexually abused girls who were institutionalized in a government shelter. Findings showed that it could be an effective tool in helping sexually abused children increase their body awareness, improve their body image and enhance self-esteem. The DMT sessions had a cathartic effect on girls since it helped them express through symbolic movement and imagery certain emotions that they may have otherwise presented.
Thesis (M.A. Guidance)--University of the Philippines Diliman.
Keywords: Sexually abused children -- Philippines -- Counseling; Dance therapy for children -- Philippines; Sexually abused children -- Institutional care -- Philippines